WHO indoor air quality guidelines on household fuel combustion: Strategy implications of new evidence on interventions and exposure–risk functions. (April 2015) - Bruce, Nigel; Pope, Dan; Rehfuess, Eva; Balakrishnan, Kalpana; Adair-Rohani, Heather; Dora, Carlos
Abstract: Background : 2.8 billion people use solid fuels as their primary cooking fuel; the resulting high levels of household air pollution (HAP) were estimated to cause more than 4 million premature deaths in 2012. The people most affected are among the world's poorest, and past experience has shown that securing adoption and sustained use of effective, low-emission stove technologies and fuels in such populations is not easy. Among the questions raised by these challenges are (i) to what levels does HAP exposure need to be reduced in order to ensure that substantial health benefits are achieved, and (ii) what intervention technologies and fuels can achieve the required levels of HAP in practice? New WHO air quality guidelines are being developed to address these issues.Aims : To address the above questions drawing on evidence from new evidence reviews conducted for the WHO guidelines.Methods : Discussion of key findings from reviews covering (i) systematic reviews of health risks from HAP exposure, (ii) newly developed exposure–response functions which combine combustion pollution risk evidence from ambient air pollution, second-hand smoke, HAP and active smoking, and (iii) a systematic review of the impacts of solid fuel and clean fuel interventions on kitchen levels of, and personal exposure to, PM2.5 and carbon monoxide (CO).Findings : Evidence on health risks from HAP suggest that controlling this exposure could reduce the risk of multiple child and adult health outcomes by 20–50%. The new integrated exposure–response functions (IERs) indicate that in order to secure these benefits, HAP levels require to be reduced to the WHO IT-1 annual average level (35 μg/m 3 PM2.5 ), or below. The second review found that, in practice, solid fuel 'improved stoves' led to large percentage and absolute reductions, but post-intervention kitchen levels were still very high, at several hundreds of μg/m 3 of PM2.5, although most solid fuel stove types met the WHO 24-hr average guideline for CO of 7 mg/m 3 . Clean fuel user studies were few, but also did not meet IT-1 for PM2.5, likely due to a combination of continuing multiple stove and fuel use, other sources in the home (e.g. kerosene lamps), and pollution from neighbours and other outdoor sources.Conclusions : Together, this evidence implies there needs to be a strategic shift towards more rapid and widespread promotion of clean fuels, along with efforts to encourage more exclusive use and control other sources in and around the home. For households continuing to rely on solid fuels, the best possible low-emission solid fuel stoves should be promoted, backed up by testing and in-field evaluation. Highlights: New WHO air quality guidelines will address household air pollution (HAP). Action on HAP could lower risk of multiple child and adult diseases by 20–50%. New evidence shows levels at or below 35 μg/m 3 PM2.5 (WHO IT-1) are needed. Most improved solid fuel stoves result in PM2.5 levels well above IT-1. Intervention strategy must shift towards accelerating access to clean fuels.